Optimalisasi Media Dakwah Dalam Upaya Pencegahan Pelecehan Seksual - Nabila Putri Sholahudin; Udin Supriadi; Nurti Budiyanti (Institut Agama Islam Negeri Kendari, 2022)
The rise of sexual harassment cases in Indonesia from year to year is very disturbing to the public, especially women. This article discusses the prevention of sexual harassment through the media of da'wah and how to optimize it. This study uses a quantitative approach. Methods of collecting data by means of a survey using a questionnaire. The results showed that 100% of respondents agreed that social media was the most effective medium in the current era in spreading da'wah against sexual harassment. However, efforts to prevent sexual harassment through social media are still not optimal. Therefore, there are several things that da'wah activists need to do in broadcasting sexual harassment, including publishing da'wah content on a regular basis, focusing on da'wah content oriented to the formation of the aqeedah of the people, and conducting social campaigns through social media.Keywords: Sexual Harassment, Social Media, Da'wah Media